Past imperfect: Hamber, B (ed) (1998) Past imperfect: Dealing with the past in Northern Ireland and societies in transition. Londonderry: INCORE & University of Ulster. ISBN 0-9533305-4-0 pbk. - Corry, Wendy (PINS-Psychology in Society, 2026)
Past imperfect is based on a conference hosted by the Initiative on Conflict Resolution and Ethnicity (INCORE) held in Belfast, Northern Ireland, in June 1998, and gathers together chapters on managing historical conflict in South Africa, Guatemala and Northern Ireland. It explores the painful complexity, diversity and necessity of remembering and truth recovery in societies with violent pasts, and helps to establish a shift in understanding social conflict as an ineradicable opposition between two sides toward understanding it as an opportunity for constructive engagement.